Changing optical nonlinearities of homoleptic bis(phthalocyaninato) rare earth praseodymium double-decker complexes by the redox reaction. (April 2017) - Ren, Boxiao; Sheng, Ning; Gu, Bing; Wan, Yong; Rui, Guanghao; Lv, Changgui; Cui, Yiping
Abstract: We report the third-order nonlinear optical properties of the homoleptic bis(phthalocyaninato) rare earth double-decker complex Pr(OOPc)2 (1 ), the oxidized species [Pr(OOPc)2 ] + (2 ), and the reduced species [Pr(OOPc)2 ] - (3 ), by performing the femtosecond-pulsed Z-scan experiments at the wavelength of 800 nm. It is found that the second-order hyperpolarizability in complex molecules decreases in the order of1 >2 >3 . More interestingly, the observed nonlinear absorption process changes from two-photon absorption in the oxidized2 to saturable absorption in the reduced3 . The results demonstrate that the nonlinear optical properties of sandwich-type phthalocyanine rare earth complexes could be altered by the redox reaction. Furthermore, the figures of merit of three complexes were evaluated for nonlinear photonic applications in optical limiter, saturable absorber, or all-optical switch. Highlights: The nonlinear optical properties of complex Pr(OOPc)2 could be altered by redox reaction. Complexes1 -3 have large nonlinear refraction index and nonlinear absorption coefficient. FOMs of the complexes are evaluated for nonlinear photonic applications.